2015
DOI: 10.1097/md.0000000000001614
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Easy-to-Use Prediction Scheme for Upper Gastrointestinal Bleeding

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Low Hb (≤10 g/dl) at baseline is, as one would expect, predictive of subsequent anemia 18. Hb less than 10 g/dl has been shown to be an independent predictor for rebleeding, need for intervention, or death following AGIB 42. In these three groups, FCM alone achieved a mean Hb increase in the range 3.0–4.6 g/dl, and the mean Hb at follow-up was normal or close to normal.…”
Section: Discussionmentioning
confidence: 91%
“…Low Hb (≤10 g/dl) at baseline is, as one would expect, predictive of subsequent anemia 18. Hb less than 10 g/dl has been shown to be an independent predictor for rebleeding, need for intervention, or death following AGIB 42. In these three groups, FCM alone achieved a mean Hb increase in the range 3.0–4.6 g/dl, and the mean Hb at follow-up was normal or close to normal.…”
Section: Discussionmentioning
confidence: 91%
“…While the incidence UGIB has been declining, mortality rate after UGIB has been maintained at approximately around 10%. [ 11 , 30 , 31 ] Several studies reported scoring systems as a way to predict the mortality of UGIB, which were large scale, multicenter studies and have undergone thorough validation processes. However, some scoring systems require endoscopic findings or more than 4 variables, or involve complex calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Management approach to children presented with UGIB was influenced by adult studies due to lack of randomized controlled studies, systematic reviews, or Cochrane reviews in children . The scoring systems for adults presented with UGIB has not been applied to children because many scores relied on endoscopic findings and were unsuitable for early classification of patients; most of the physiological and hematological parameters on which they were based were not applicable to children . We tried to compare the scoring systems (Glasgow–Blatchford score, the clinical Rockall score, and AIMS) to a new scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…Yearly incidence of UGIB ranges from 10–18/10 000 in adults in comparison with 1–2/10 000 in children . The most frequent causes are peptic ulcers (46%), followed by esophagitis and erosions in adults . For children, the etiology of UGIB varies in different parts of the world, presenting geographical alterations in common disease states …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation